Comparing Alternative Methods of Measuring Skin Color and Damage - Daniel, Lauren C. (2008)
OBJECTIVE: The current study investigated the reliability and validity of several skin color and damage measurement strategies and explored their applicability among participants of different races, skin types, and sexes. METHODS: One hundred college-aged participants completed an online survey about their perceived skin damage and skin protection. They also attended an in-person session in which an observer rated their skin color; additionally, UV photos and spectrophotometry readings were taken. RESULTS: Trained research assistants rated the damage depicted in the UV photos reliably. Moderate to high correlations emerged between skin color self-report and spectrophotometry readings. Observer rating correlated with spectrophotometry rating of current but not natural skin color. Lighter-skinned individuals reported more cumulative skin damage, which was supported by UV photography. Although women's current skin color was lighter and their UV photos showed similar damage to men's, women reported significantly more damaged skin than men did. CONCLUSIONS: These findings suggest that self-report continues to be a valuable measurement strategy when skin reflectance measurement is not feasible or appropriate and that UV photos and observer ratings may be useful but need to be tested further. The results also suggest that young women and men may benefit from different types of skin cancer prevention interventions.